Informational and Interpersonal Justice as Mediators Between Trasnformational Leadership and Cynicism Toward Organizational Change - Muhammad Delphino; Wustari L. Mangundjaya (Greenation Publisher, 2024)
This study investigates the factors that can predict the emergence of cynicism about organizational change, which is defined as a pessimistic outlook for successful change with blame placed on